Effect of Air Flow on Drying Stevia Rebaudiana using Solar Dryer Greenhouse - Nurhadianty, Vivi; Dewi, Luthfi Kurnia; Sarosa, Aji Hendra; Muttaqim, Moch Fitron; Hidayat, Fahrul Huzain (Jurnal Rekayasa Mesin, 2026)
A phenomenon known as the greenhouse effect happens when solar radiation is trapped and heats the planet. This effect is useful for drying agricultural materials. One of the natural sugar substitutes that is dried during production is stevia rebaudiana. This research aims to determine the effect of air flow rate in drying using a solar greenhouse dryer on the water content and drying rate of stevia leaves. The Variable of the air flow rate used are 155 cm/s, 135 cm/s, natural and will be dried for 1, 2, 3, 4, 5, and 6 hours in the Solar Dryer Greenhouse. The stevia's water content was measured with a thermogravimetric. The results showed drying stevia using the Greenhouse Solar Dryer with an air flow rate of 155 cm/s produced the best drying performance with a decrease in the water content of stevia leaves of 89.7% and the highest drying rate of 21.3 kg H2O/kg solids.